A gender provocation - Loh, Seow Shi (2016)
Findings from 5 nonparticipant observations and 20 semi-structured interviews conducted with students of Nanyang Technological University were utilized to study the perceptions of teaching professionals. Interactions within the university classroom were surveyed to investigate the role of gender relations affecting faculty and student interaction. In addition, variables such as individual attributes, faculty conduct, gender expectations and power sensitivity were found to be essential in contributing to students’ overall perceptions.